Research hotspots and frontiers of cluster headaches: a bibliometric analysis - Mao, Qiangjian; Xu, Shiqi; Wang, Yuqing; Wu, Desheng; Huang, Guomin; Li, Ziru; Zhang, Xiaoming; Chi, Zhenhai (Frontiers in Neurology, 2024)
Background: Extensive research on cluster headaches (CHs) has been conducted worldwide; however, there is currently no bibliometric research on CHs. Therefore, this study aimed to analyze the current research hotspots and frontiers of CHs over the past decade. Methods: Raw data on CHs was obtained from the Web of Science Core Collection database from 2014 to 2023. CiteSpace V6.2 R7 (64 bit) and Microsoft Excel were used to assess the annual publication volume, authors, countries, and references. VOSviewer 1.6.19 software was used to assess the institutions, cited authors, and keywords, and co-occurrence and clustering functions were applied to draw a visual knowledge map. Results: In the past decade, the overall annual publication volume of articles related to CHs has increased year by year, showing promising development prospects. The total 1909 articles contained six types of literature, among which the proportion of original research articles was the highest (1270 articles, 66.53%), published in 201 journals. Cephalalgia (439 articles, 23.00%) had the highest publication volume, and the Lancet was the journal with the highest impact factor (IF = 168.9). Furthermore, the United States of America was the country with the most published papers(584 articles, 30.60%), University of London was the research institution with the most published papers(142 articles, 7.44%), and Goodsby, Peter J was found to be the most prolific author (38 articles, 1.99%). Conclusion: This study may provide some direction for subsequent researcher on CHs. The hotspots and frontiers of future research on CHs are suggested as follows: in basic medicine, more attention should be paid to pathophysiology, especially on increasing research on the pathogenesis mediated by CGRP; in clinical medicine, more attention should be paid to the design of evidence-based medicine methodology, especially the strict design, including double-blind, questionnaire, and follow-up, in randomized controlled trials, using high-quality articles for meta-analyses, and recommending high-level evidence; therapeutic techniques need to be further explored, suggesting the implementation of transcranial magnetic stimulation of the cortex, and stimulation of the sphinopalatine ganglia and occipital nerve to achieve peripheral neuromodulation. Furthermore, chronic migraine and insomnia are inextricably linked to CHs.